The Pharmacokinetics, Metabolism, and Clearance Mechanisms of Tofacitinib, a Janus Kinase Inhibitor, in Humans - Dowty, Martin E.; Lin, Jinyan; Ryder, Tim F.; Wang, Weiwei; Walker, Gregory S.; Vaz, Alfin; Chan, Gary L.; Krishnaswami, Sriram; Prakash, Chandra (Drug metabolism and disposition, 2014)
Tofacitinib is a novel, oral Janus kinase inhibitor. The objectives of this study were to summarize the pharmacokinetics and metabolism of tofacitinib in humans, including clearance mechanisms. Following administration of a single 50-mg 14C-labeled tofacitinib dose to healthy male subjects, the mean (standard deviation) total percentage of administered radioactive dose recovered was 93.9% (±3.6), with 80.1% (±3.6) in the urine (28.8% parent), and 13.8% (±1.9) in feces (0.9% parent). Tofacitinib was rapidly absorbed, with plasma concentrations and total radioactivity peaking at around 1 hour after oral administration. The mean terminal phase half-life was approximately 3.2 hours for both parent drug and total radioactivity. Most (69.4%) circulating radioactivity in plasma was parent drug, with all metabolites representing less than 10% each of total circulating radioactivity. Hepatic clearance made up around 70% of total clearance, while renal clearance made up the remaining 30%. The predominant metabolic pathways of tofacitinib included oxidation of the pyrrolopyrimidine and piperidine rings, oxidation of the piperidine ring side-chain, N-demethylation and glucuronidation. Cytochrome P450 (P450) profiling indicated that tofacitinib was mainly metabolized by CYP3A4, with a smaller contribution from CYP2C19. This pharmacokinetic characterization of tofacitinib has been consistent with its clinical experience in drug-drug interaction studies.